Perlindungan Hukum Terhadap Praktik Kedokteran Gigi di Indonesia: Studi Kasus Terhadap Tanggung Jawab Profesional - Zirran Dhashytha Elzhar (PSHPM Untag Semarang, 2025)
The legal protection of dental practice in Indonesia remains a critical issue due to significant gaps in regulation, implementation, and law enforcement. This study explores weaknesses in existing legal frameworks, focusing on the insufficient specificity of Law No. 29 of 2004 regarding dental procedures requiring specialized skills. The lack of detailed Standard Operating Procedures (SOPs) exacerbates these gaps, creating uncertainty for both patients and practitioners. Factors such as limited understanding of legal and ethical standards among dentists, inadequate oversight mechanisms, and challenges posed by the digital age, including the rise of illegal dental practices via social media, further compound the issue. Through normative legal analysis and case studies, including Supreme Court Decision 557 PK/Pdt/2017, this research highlights the pressing need for regulatory reform and enhanced law enforcement. Recommendations include revising existing laws to incorporate clearer guidelines for dental practices, ongoing education for practitioners and the public, and integrating technology into monitoring and reporting systems. These measures aim to create a safer and more professional dental healthcare system, ensuring justice and legal certainty for all stakeholders.